2019
DOI: 10.37002/revistacepsul.vol8.663eb2019001
|View full text |Cite
|
Sign up to set email alerts
|

Zooplâncton da Baía da Babitonga e plataforma continental adjacente: diagnóstico e revisão bibliográfica

Abstract: O zooplâncton é um importante elo nas teias tróficas aquáticas, além de representar uma parcela considerável da biodiversidade. No presente estudo, revisamos o conhecimento sobre a comunidade zooplanctônica no estuário da Babitonga e áreas costeiras adjacentes visando fornecer subsídios para elaboração de planos de conservação e manejo locais. O estudo do zooplâncton na região é recente, desde 2002, com maior esforço amostral no canal principal do estuário. Um total de 261 espécies foram registrados até o mome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
(27 reference statements)
1
1
0
Order By: Relevance
“…Most of the species captured in the present study are euryhaline and typically found in warm brackish-water ecosystems worldwide (Devassy & Goes 1988, Sassi 1991, Huang et al 2004, Li et al 2006, Madhu et al 2007, Araujo et al 2008, Dias et al 2018. The abundance and diversity levels, as well as species composition and assemblage structure of both zoo and phytoplankton found here can be considered as typical of winter conditions from BBE and other nearby Southwestern Atlantic subtropical estuaries (Montú & Cordeiro 1988, Brandini et al 2006, Miyashita et al 2012, Salvador & Bersano 2017, Nogueira Júnior & Costa 2019.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Most of the species captured in the present study are euryhaline and typically found in warm brackish-water ecosystems worldwide (Devassy & Goes 1988, Sassi 1991, Huang et al 2004, Li et al 2006, Madhu et al 2007, Araujo et al 2008, Dias et al 2018. The abundance and diversity levels, as well as species composition and assemblage structure of both zoo and phytoplankton found here can be considered as typical of winter conditions from BBE and other nearby Southwestern Atlantic subtropical estuaries (Montú & Cordeiro 1988, Brandini et al 2006, Miyashita et al 2012, Salvador & Bersano 2017, Nogueira Júnior & Costa 2019.…”
Section: Discussionsupporting
confidence: 51%
“…Previous studies in the BBE have showed that the salinity gradient is one of the most important factors structuring the horizontal distribution of planktonic communities (Brandini et al 2006, Costa & Souza Conceição 2009, Nogueira Júnior & Oliveira 2017. However, plankton distribution has been previously analyzed only considering seasonal time-scale, and nothing is locally known about short-term dynamics (Nogueira Júnior & Costa 2019). In the present study, we aim to test differences in the horizontal structure of the phyto and zooplankton assemblages during ebb and flood tide in this mixed estuary.…”
Section: Introductionmentioning
confidence: 99%